Status of Comorbid Congenital Anomalies and Their Influence on Resource Use in Pediatric Inpatients: A Serial Cross-Sectional Study in Shanghai, China - Jianwei Shi; Jianwei Shi; Ning Chen; Wenya Yu; Rui Liu; Hua Jin; Zhaohu Yu; Li Luo; Li Gu; Rong Yang; Qian Liu; Wei Feng; et al. (Frontiers Media S.A., 2020)
Objectives: The status of children with comorbid congenital anomalies (CAs) and their effects on related hospital resource utilization have been minimally investigated. We aimed to describe the congenital anomalies comorbidity status and their effects on hospital resource utilization (length of stay, cost) by pediatric patients.Setting: This study was conducted in five tertiary care children's hospitals in Shanghai, China.Participants: Data were obtained from the inpatients' electronic health records; diagnoses were recorded using International Classification of Disease, Ninth Revision codes. In total, 7,890 children were diagnosed with congenital anomalies (13.13%), which were either primary or secondary.Primary and secondary outcome measures: The dependent variables were length of stay and cost. The independent variables were demographic and clinical characteristics and CA status.Results: In total, 50.98% of the hospitalized patients had comorbid CA conditions. Medical+CA patients were associated with a longer LOS (β = 2.656, P < 0.001), and CA+medical patients were associated with higher costs (β = 7.222, P < 0.001). Cardiovascular, musculoskeletal, and genitourinary diseases were the top three comorbid diseases. The average LOS for the top three comorbid diseases was longest in the medical+CA group, followed by CA+medical group. Cardiovascular disease was the most frequent comorbidity (ranking 1 in the medical+CA group and 2 in the CA+medical group), and the cost of cardiovascular disease was highest in all groups.Conclusions: A high prevalence of comorbid CA conditions was observed among pediatric inpatients in the sampled tertiary hospitals in China. Strategic planning should be improved to guide resource utilization for complex comorbid CA care.